Kewirausahaan Berbasis Rumah Tangga: Studi Usaha Pada Rumah Produksi Mama Chika - Hattab, Syahruddin; Nelsa; Nurhidayati, Arifa; Soande, Faustino Andresta; Bakar, Chandra Abu; Mado, Moh. Arzal Saputra (JPS: Journal of Publicness Studies, 2025)
This study aims to describe the business profile, operational processes, marketing strategies, and challenges faced by Mama Chika Production House MSME as one of the local food businesses in Palu City. This study also seeks to identify factors that influence business sustainability, particularly in the context of managing fried onions and silkworm sticks as regional specialty commodities. The research method used is a qualitative approach through direct observation and in-depth interviews with business owners. The results show that this business was born from a combination of humanitarian motivation, environmental concerns, and family economic needs during the pandemic. Business management is carried out by utilizing local labor, maintaining production quality through direct supervision by the owner, and expanding marketing reach through partner networks and social media. The main challenges faced include fluctuations in raw material prices, scarcity of onion supplies, and ecological factors that affect crop quality. Nevertheless, Mama Chika Production House has been able to survive and continue to grow through simple but effective operational strategies and extensive distribution partnerships.